Penyusunan Model Konsepsual Basisdata untukSistemlnformasiKadasterMultiguna - Rochmad Muryamto (Faculty of Engineering, Universitas Gadjah Mada, 2003)
The term of nrultipurpose cadastre is used to describe a system that is designed to record'store, and provide not only landlenure and land valuation idormation but also a wide varietyof information that ,o, u,u f*rtionally related to and referenced by property parcels' It meansthat multipurpose no,t oniy ,eceiues information and data from many sources' but it alsoprovides services and products for many purposes and users' The research is directed to designa conceptual model oi mltipuipose cadastre database for developing its information system'The conceptual model was developed using entity relationship diagram and represented inrelational database structure. A model of multipurpose cadastre,was also developed using someparcel based data that came fronr many ,)ur)rr. The model was situated in KelurahonTahunan, Yogtakarta'An information system of multipurpose cadastre based on the conceptual design can bedeveloped and it provided nol onlyiudicial andfiscal information' but also semices informationsuch as water, telephone, and electricity. In addition, some problems occurred in building themodel were also discussed'Keywords: multipurpose cadastre' conceptual design